Relationship Between Enterpreneurial Orientation and Performance of Family Owned Enterpries in Nairobi County: Enterpreneurial Orientation and Performance of Family Owned Enterprises in Nairobi County - Mburu, Racneal Mugure; Gichira, Robert; Kyalo, Teresiah (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
Small and Medium Family Owned Enterprises (SMFEs) are the engines of economic development through job creation and poverty reduction in any nation. Currently, the SMFEs sector in Kenya contributes over 70% of the country’s GDP. This is in spite of the challenges surrounding this vital sector including low performance as compared to non family enterprises, high mortality rate especially after the founder exits, lack of finances among others. The study seeks to establish the relationship between entrepreneurial orientation and small and medium family owned enterprises performance in Kenya. The specific objectives are to find out the role of innovativeness, risk taking and proactiveness in the performance of family owned enterprises in Kenya. Parker’s Theory of Proactiveness and Schumpeter’s theory of innovation were the theoretical framework for this study. Cross sectional survey design was adopted. The study population was the manufacturing family owned enterprises registered by Kenya Association of Manufacturers based in Nairobi City County. The respondents were the Founders, C.E.Os, Directors and Managers of the firms. Data was collected using a questionnaire and the quantitative data was analyzed by calculating the response rate with descriptive statistics such as mean, statistical deviation and proportion using Statistical Packages for Social Scientists (SPSS) version 21 and Microsoft Excel. Inferential data analysis was carried out by the use of factor correlation analysis to determine the strength and the direction of the relationship between the dependent and the independent variables. A regression model was fitted and hypothesis testing carried out using multiple regression analysis. Results of the study revealed a positive and significant relationship between innovativeness, risk taking and proactiveness on firm performance.